Probabilistic assessment of creep-fatigue crack propagation in austenitic stainless steel cracked plates - Vojdani, Ali; Farrahi, Gholam Hossein; Mehmanparast, Ali; Wang, Bin (Elsevier, 2018)
This study investigates the effects of uncertainties in the prediction of creep-fatigue crack propagation in 316L(N) austenitic stainless steel plates containing a semi-elliptical surface defect. Different parameters in geometry, material behavior and test condition are considered as random variables in probabilistic assessments. Monte-Carlo sampling method is employed to estimate the probability distribution of desired outputs such as propagated crack sizes, stress intensity factors and creep rupture life. It is shown that, the standard deviation of the predicted crack sizes in both through-wall direction and along the surface of the plate will be increased by increasing the time (hence the crack size). It is observed also that, the uncertainty in the prediction of the half-surface crack lengths, ci, is significantly more than that of crack depths, ai. Furthermore, probabilistic evaluations are performed using different reliability methods to calculate the probabilities of exceedance of available experimental results. These evaluations clarified the importance of consideration of uncertainties in creep-fatigue crack growth prediction. Sensitivity analyses are carried out to provide useful information about the order of importance of random variables associated to the different limit state functions. It is found that, the CoV (Coefficient of Variation) of the initial crack size, a0 and c0/a0 has a significant role on the importance of these parameters; and therefore they may be important random variables in such probabilistic assessments, based on their CoV and defined limit state functions.
Keywords: Creep-fatigue; Crack growth; Probabilistic assessment; Uncertainty